Midterm results of Salter and Pemberton pelvic osteotomies for developmental dysplasia of the hip - Incesu, Mustafa; Belhan, Oktay; Karakurt, Lokman (Turkish Joint Diseases Foundation, 2007)
Objectives: The aim of this study was to compare the clinical and radiographic results of Salter and Pemberton pelvic osteotomies in developmental dysplasia of the hip (DDH). Patients and methods: Thirty-three patients (43 hips) with DDH were retrospectively evaluated. Twenty-three patients (29 hips) underwent Salter (SPO), 10 patients (14 hips) underwent Pemberton (PPO) osteotomies. The mean age was 40.5 months (18 to 130 months) in the SPO group, and 27 months (18 to 52 months) in the PPO group. One-staged surgery was performed in all the patients. Following open reduction, pelvic and/or femoral osteotomies were performed. In patients with a thin iliac wing and adequate acetabular width, PPO was preferred, otherwise SPO was the choice. The acetabular index (AI) and center-edge (CE) angles were measured on pre- and postoperative radiographs. Radiographic and clinical results were assessed according to the Severin and modified McKay criteria, respectively. The mean follow-up was 38 months (12 to 75 months) in the SPO group, and 33 months (12 to 64 months) in the PPO group. Results: The mean postoperative AI and CE angles significantly improved in both groups (p < 0.05), being 21.9 degrees (54.6%) and 28.7 degrees with SPO, 21.4 degrees (58%) and 27.9 degrees with PPO, respectively. Excellent and good results in the SPO and PPO groups accounted for 89.7% and 78.6% according to the Severin criteria, and 93.1% and 78.6% according to the modified McKay criteria, respectively. The most common complication was avascular necrosis (18.6%). The two groups did not differ significantly with respect to improvements in the AI and CE angles, radiographic and clinical results, and the incidence of avascular necrosis (p > 0.05). Conclusion: Both osteotomy methods were found to be safe and successful for the treatment of DDH with anterolateral acetabular deficiency.
Keywords: femur head necrosis/complications; hip dislocation; congenital/surgery; osteotomy/methods